2008
DOI: 10.1002/ijc.23758
|View full text |Cite
|
Sign up to set email alerts
|

Four potential biomarkers as prognostic factors in stage III serous ovarian adenocarcinomas

Abstract: The mortality rate for patients with ovarian carcinomas is high and the available prognostic factors are insufficient. The use of biomarkers may contribute to better prediction and survival for these patients. We aimed to study the gene and protein expressions for 7 potential biomarkers, to determine if it is possible to use them as prognostic factors. Genes selected from our previous microarray analysis (2006), CLU, ITGB3, TACC1, MUC5B, CAPG, PRAME and TROAP, were analyzed in 19 of the tumors with quantitativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
48
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(54 citation statements)
references
References 48 publications
6
48
0
Order By: Relevance
“…In the present study, the expression and function of CapG in CRC were investigated, and the results demonstrated that the expression level of CapG protein in CRC tissue was significantly higher than in non-tumor tissue. This observation was consistent with the results of studies regarding other types of cancer, including oral (18), pancreatic (19), ovarian (20)(21)(22) and breast cancer (23). In the present study, the positive expression of CapG in the cytoplasm and nucleus was significantly associated with CRC location, differentiation, LMN status and clinical stage.…”
Section: Discussionsupporting
confidence: 93%
“…In the present study, the expression and function of CapG in CRC were investigated, and the results demonstrated that the expression level of CapG protein in CRC tissue was significantly higher than in non-tumor tissue. This observation was consistent with the results of studies regarding other types of cancer, including oral (18), pancreatic (19), ovarian (20)(21)(22) and breast cancer (23). In the present study, the positive expression of CapG in the cytoplasm and nucleus was significantly associated with CRC location, differentiation, LMN status and clinical stage.…”
Section: Discussionsupporting
confidence: 93%
“…CapG overexpression has been reported in several cancer types, such as breast carcinoma (Kang et al, 2010;Xu et al, 2010), ovarian adenocarcinoma (Partheen et al, 2008), oral carcinoma (Nomura et al, 2008), pancreatic cancer (Thompson et al, 2007a,b), and ocular melanoma (Van Ginkel et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Significant overexpression of the CapG protein was detected in pancreatic cancer (Thompson et al 2007) and oral squamous-cell carcinoma (Nomura et al 2008), with associations with large tumor size and advanced staging in the case of oral squamous-cell carcinoma. CapG is also expressed at higher levels in ovarian carcinomas with possible correlations with advance disease stage and survival (Partheen et al 2008). Our results showed that lung adenocarcinoma tissues had significantly increased expression of CapG immunoreactivity compared to adjacent tumor-free tissues.…”
Section: Discussionmentioning
confidence: 52%